UNDERSTANDING THE PERCEIVED BARRIERS AND FACILITATIONS OF STUDENT SPORTS PARTICIPATION: A CASE STUDY OF GOMAL UNIVERSITY DERA ISMAIL KHAN - Wasim Khan; Tasleem Arif; Fida Hussain (The Sky)
This research study was conducted to quantify the ratio of students’ involvement and non-involvement in sport participation. Moreover, reasons for non-involvement and influential factors in their way to participate in sport were also taken into consideration. A sample of n=375 (334 males; 41 females) were included in the survey. A closed-ended questionnaire was properly developed and used to obtain the required data. Frequency and percentage were applied to analyze the collected information with the help of a computer software. Analysis of the study indicated that 91.1% students participated in sport while, 8.8% did not take part in sport. Analysis of the study interpreted that lack of maintenance of the ground, lack of confidence to compete, fear of injury, insufficient to influence time and insufficient to influence commitment were considered barriers that influence sport’s participation among students. Similarly, the analyzed data revealed that low income, lack of passion and interest, dominancy of competitive sports and academic stress are influential factors contributing to nonparticipation in sport. the findings are critical for university policymakers, when it comes to developing and promoting sport and other recreational sports